Lail Adventure: Perancangan Infrastruktur Pengembangan Game Edukasi Menggunakan Metode Object-Oriented Programming (OOP) - Hariyadi; Farras Danyka Putra Farras; Aminudin (Jurnal Repositor, 2026)
Industry 4.0 era has shifted the educational paradigm towards skills in information-seeking, problem-solving, and creativity. Challenges arise in integrating technology into curricula, particularly in leveraging children's interest in games for educational purposes. This research develops an Islamic educational game named Lail Adventure, which introduces Muhammadiyah values using Object-Oriented Programming (OOP) with Java and the Greenfoot framework. The main results include a model of inheritance and polymorphism concepts in the game, enabling efficient task management and flexible adjustments. The benefits of OOP include increased modularity and efficiency in game development, despite challenges in understanding its concepts. This research provides a foundation for developing interactive educational games that integrate educational values with technology, enriching children's learning experiences in Muhammadiyah studies.